Association of Nutritional Status and Physical Activity Level with Pneumonia in Indonesian Urban Area - Setyowati, Yuli Dwi; Suryatma, Anton; Puspita, Tities (Jurnal Gizi dan Pangan, 2020)
The study aimed to overview and analyze the relationship between nutritional status, physical activity and pneumonia in a community in South Jakarta. We analyzed the secondary data from the 2016‒2018. The Programme of Knock on Doors and Serve with Heart (Ketuk Pintu Layani Dengan Hati) (KPLDH) census for the Tebet District in South Jakarta. The census involved 58,627 samples, which were divided into three age groups: children <5 years old, adolescents, and adults. We measured the nutritional status of children <5 years old using the Weight/Height Ratio (WHR) category (z-score), adolescents with Body Mass Index (BMI)/age (z-score) and adults with BMI (kg/m2). Physical activity was measured for adults and adolescent only and categorized as “routine” and “non-routine”. The highest prevalence of pneumonia was found in samples with non-routine physical activity and in adults. Most of the adults who had pneumonia were also had normal nutritional status. Adults with Chronic Energy Deficiency (CED) and Severe CED (S-CED) had a higher risk of having pneumonia OR=8.465; CI 95%=5.478‒13.081 for S-CED and OR=3.210; p<0.05; CI 95%=1.895‒5.438 for CED respectively compared to those with normal weight. Adults and adolescents with routine physical activity had a lower risk of having pneumonia (OR=0.496; 95% CI: 0.320‒0.767). Further studies are also needed concerning the relationship of pneumonia with other determinants such as socio-economic status, environmental issues, and nutritent intake.